The confessions : a novel - Carr, Paul Bradley (Atria Books, 2025)
As a global supercomputer shuts down and anonymous letters expose humanity's darkest acts, former nun Maud Brookes and tech CEO Kaitlan Goss navigate a collapsing society and their own buried truths, each seeking to outmaneuver the other as they attempt to restore order.